Various amide-derived ligands induced five octamolybdate-based metal–organic complexes: synthesis, structure, electrochemical sensing and photocatalytic properties. Issue 30 (12th April 2021) - Wang, Xiuli; Li, Lei; Wang, Xiang; Zhang, Yuqing
Abstract : Five octamolybdate-based complexes with diverse architectures employing three new amide-derived organic ligands can be used as promising electrochemical sensors and photocatalysts. Abstract : By designing and introducing three new amide-derived ligands, {L 1 = 4-[(1 H -imidazole-4-carboxamide)ethyl]phenyl-1 H -imidazole-4-carboxamide, L 2 = bis[4-(1 H -imidazole-4-carboxamide)phenyl]methanone and L 3 = N -(quinolin-5-yl)-1 H -pyrazole-3-carboxamide}, into the reaction system based on different metal ions and polymolybdate, five octamolybdate-based complexes, [CoL 1 (β-Mo8 O26 )0.5 ] (1 ), [M(H2 O)2 L 2 (β-Mo8 O26 )0.5 ][M = Co (2 ) and Ni (3 )] and [M(HL 3 )2 (β-Mo8 O26 )][M = Co (4 ) and Zn (5 )], have been successfully prepared and structurally characterized. The three ligands were designed and used for the construction of polyoxometalated-based metal–organic complexes for the first time. Complexes 1–5 show 2D supramolecular structures, and their remarkable structural feature is that the coordination between metal ions, octamolybdate and organic ligands generated diverse architectural segments. A 1D ladder-like chain in complex 1 was formed by using the L 1 ligand, where the Co–L 1 metal–organic chain acted as the "sides" of the ladder and the polyoxoanion acts as the "middle rails", but a 1D wave-like metal–organic M–L 2 chain for the L 2 ligand in 2 and 3, and a 1D fence type chain for the L 3 ligand in 4 and 5 were formed . In addition, the effect of amide-derived ligands on the final structures of the title complexes was discussed. The electrocatalytic and electrochemical sensing towards bromate, nitrite, Cr(vi ) and Fe(iii ) ions, as well as the photocatalytic activities for organic dyes of the title complexes were also investigated. Complexes 1 and 5 exhibit remarkable current responses in the determination of trace Cr(vi ) and Fe(iii ) ions, and complex 5 displays a superior lower detection limit, which can reach 0.7 μM.